Soil Salinization and Its Effect on Agricultural Lands in Samarra District - Muhammad, Adnan Attia; Mohammed, Iyad Ansif Jassim (Journal of Tikrit University for Humanities, 2022)
The problem of salinity is one of the serious problems that negatively affect the agricultural lands in the study area, as it poses a clear danger to the agricultural development in it, as well as its variation from one region to another, and in varying degrees. Within the study area and determining the proportions of salts in it, identifying the discrepancy between the proportions of salts and their geographical distribution and indicating the role of the causative factors represented by natural factors, including surface, climate, soil and water resources, which contribute to increasing or decreasing salinity in them, as well as human factors represented by irrigation projects, drainage, cultivation and wrong methods such as waste, not following agricultural rotations and wrong plowing, as well as a statement of the most important salinity areas within the study area through the results of laboratory analyzes, and a statement of the most important means and treatments for salinized lands in order to determine how to reduce the impact of salinity within certain standards and to reclaim agricultural lands to achieve the optimal investment for these lands according to An organized strategy to achieve economic development within the study area, as well as a statement of its impact on the productivity of agricultural crops through information obtained from farmers. The study showed that one of the most important natural factors affecting is the climate, especially the high temperature and the increase in the amount of evaporation, which led to the accumulation of salts from irrigation water, whether surface or underground, as well as the salts in the soil itself. The human factors were no less important in exacerbating the problem of salinity, as it appeared to mismanage the land from the lack of use Water rationing, not using the agricultural cycle, and not following scientific methods played a major role in its spread. The study also showed that salinity levels vary from one region to another, and a number of natural and human factors have combined to paint a picture of this discrepancy. As a result of the variation in the picture of salinity distribution, the productivity of crops varied between one region and another, and one crop and another, according to the degree of tolerance of the crops to soil salinity.